Off-equilibrium sphaleron transitions in the glasma - Mace, Mark; Schlichting, Sören; Venugopalan, Raju (Physical review, 2016)
We perform the first, to our knowledge, classical-statistical real time lattice simulations of topological transitions in the nonequilibrium glasma of weakly coupled but highly occupied gauge fields created immediately after the collision of ultrarelativistic nuclei. Simplifying our description by employing SU(2) gauge fields, and neglecting their longitudinal expansion, we find that the rate of topological transitions is initially strongly enhanced relative to the thermal sphaleron transition rate and decays with time during the thermalization process. Qualitative features of the time dependence of this nonequilibrium transition rate can be understood when expressed in terms of the magnetic screening length, which we also extract nonperturbatively. A detailed investigation of autocorrelation functions of the Chern-Simons number (NCS) reveals non-Markovian features of the evolution distinct from previous simulations of non-Abelian plasmas in thermal equilibrium.
Gesehen am 22.05.2020